2011
DOI: 10.1097/qad.0b013e3283423219
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage in adipose tissue of untreated HIV-infected patients

Abstract: in nonlipodystrophic HIV-infected naive patients, viral infection is associated with adipose tissue mtDNA decrease and mitochondrial dysfunction independently of antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
1
33
1
1
Order By: Relevance
“…Detections such as these provide metabolic information linked to patient health and could serve as a guide for the implementation of corrective therapy prior to the development of clinical symptoms. Key metabolic defects caused by HIV also include its ability to induce malnutrition, 18 disrupt the functioning of the mitochondria, 19,20 induce changes in body composition, fat distribution, changes in lipid, carbohydrate and protein metabolism. 14,16 Changes in body composition are largely attributed to an increase in the catabolic state of the host.…”
Section: Hiv-and Haart-associated Metabolic Changes (As Detected By Cmentioning
confidence: 99%
“…Detections such as these provide metabolic information linked to patient health and could serve as a guide for the implementation of corrective therapy prior to the development of clinical symptoms. Key metabolic defects caused by HIV also include its ability to induce malnutrition, 18 disrupt the functioning of the mitochondria, 19,20 induce changes in body composition, fat distribution, changes in lipid, carbohydrate and protein metabolism. 14,16 Changes in body composition are largely attributed to an increase in the catabolic state of the host.…”
Section: Hiv-and Haart-associated Metabolic Changes (As Detected By Cmentioning
confidence: 99%
“…73 More recently, Garrabou et al found significant mtDNA depletion and reduced mitochondrial oxidative function in adipocytes of HIVinfected ART-naïve individuals compared to uninfected controls. 74 The value of tissue mtDNA measurement has been questioned by Kim et al, 75 who confirmed findings of depleted mtDNA in adipose tissue of lipoatrophic HAART-treated patients, but found no decrease in mtDNA-dependent mitochondrial function and an actual compensatory increase in nuclear-driven mitochondrial biogenesis, suggesting that mtDNA depletion was not a good marker for mitochondrial function. In another cross-sectional study by Magaard et al, 34 mitochondrial DNA was lower in muscle biopsies from 24 patients with HIV on HAART than 10 ART-naïve HIV patients, but both groups demonstrated decreased PBL mtDNA compared to 11 healthy controls.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitmentioning
confidence: 81%
“…In part this is because these drugs are often prescribed as one component of highly active antiretroviral cocktails of drugs, which also may be increasing mutational load. In addition, HIV infection itself can damage mitochondria [35,36] For both HepG2 and CCD-1112Sk cells, the frequency of mutations was higher for the AZT treated samples. 11A 24A 64T 80A 128C -382A -396C 181A 198G 295A 320A -345A 369A -382C -388A 369A -388A 382A -396C 388A CO 2 7830G 7918T -7966T -8117T 7982C 7982C-8019T 7985T 7986G ND1 3573A -3632A -3670A 3905G 3993C…”
Section: Discussionmentioning
confidence: 99%